Corpos estranhos de seio maxilar - Roberto Campos Meirelles; Ciríaco Cristóvão Tavares Atherino (Revista do Colégio Brasileiro de Cirurgiões)
The authors present five cases of maxillary sinus foreign bodies, four of them (80%) originated from surgical problems. They discuss their findings, enphasizing the difficulty and the importance of early diagnosis and treatment. They recommend the use of tied gauze in the surgical procedures in the maxillary sinus.